THE LEGAL FORCE OF CROSS COLLATERAL AGREEMENT ON MORTGAGE OBJECTS UNDER INDONESIAN LAW - Rahimy, Aziz (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Currently, the risk appetite of banks and other formal financing institutions in Indonesia still consider collateral as the main factor to guarantee debt repayment. For the purpose of collateral availability, there is a practice of pledging based on a cross-collateral agreement. However, the practice of cross collateral still raises legal issues in its implementation, especially regarding the legal force of the cross collateral agreement to the mortgage object. This issue will also have an impact on the executorial rights to the object of the mortgage, if the debtor defaults on the other debt. Based on the research results, it is known that to bind an object of mortgage rights as collateral for the repayment of more than one debt, it can be done by binding the object of mortgage rights based on a ranking system with the concept of senior-junior, or by making a cross-collateral agreement contractually based on the principle of contract law with an open system. To provide legal certainty and legal protection to creditors, agreements with cross collateral clauses need to be supported by a cross default clause which regulates that the main obligation in a contract becomes an obligation in another contract, and makes default due to non-fulfillment of the main obligation on a contract, become a default on another contract. So that this cross collateral agreement can provide binding legal force and creditors can execute based on the Mortgage Rights Law.